2021
DOI: 10.1177/1048291120982597
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Opioid Awareness Through a Union-Based Peer Training Model

Abstract: Work factors, including physical job demands, appear to be risk factors for opioid overdoses. We collaborated with unions representing workers in high-risk occupations and offered resources to develop tailored educational interventions for their members. An ironworkers’ local, a statewide nurses’ union, and a Teamsters local union participated, at levels higher than we had anticipated. The three unions trained 285 workers, including apprentices, stewards, and those nearing retirement. Short surveys assessed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, the training under study here closely models the aims of worker opioid awareness training developed for other high-risk sectors [28,32]. Our results align with those of a recent evaluation of a longer-format opioid hazards prevention training developed for the National Institute of Environmental Health Sciences Worker Training Program and with the results reported from a training program for workers in construction, nursing, and material moving occupations [29,33].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the training under study here closely models the aims of worker opioid awareness training developed for other high-risk sectors [28,32]. Our results align with those of a recent evaluation of a longer-format opioid hazards prevention training developed for the National Institute of Environmental Health Sciences Worker Training Program and with the results reported from a training program for workers in construction, nursing, and material moving occupations [29,33].…”
Section: Discussionsupporting
confidence: 81%
“…The training presentation was developed from discussion with mine safety trainers and mine operators and from previously developed trainings for construction workers and others [28,29]. The training content included recognizing which medications are opioids, work-related risk factors for opioid use, prevention strategies such as ergonomics and tips for the doctor's office, and "harm reduction" approaches such as avoiding stigmatizing attitudes that discourage helpseeking and preventing fatal overdoses through the use of naloxone.…”
Section: Intervention and Participantsmentioning
confidence: 99%
“…30,31 This is addressed in several articles in this special issue. In “Promoting Opioid Awareness Through a Union-Based Peer Training Model,” Roelofs et al 32 describe an opioid awareness union-based peer training model implemented in collaboration with union locals of the Ironworkers’ and Teamsters, and a state-wide nurses’ union, along with an evaluation of the impact of the training program. Training evaluations revealed positive changes in opioid knowledge, the stigma around help-seeking, and confidence in helping others with substance use disorder (SUD).…”
Section: Importance Of Worker Training and Union-based Programsmentioning
confidence: 99%
“…30,31 This is addressed in several articles in this special issue. In "Promoting Opioid Awareness Through a Union-Based Peer Training Model," Roelofs et al 32 In "Opioids and the Workplace Prevention and Response Awareness Training: Mixed Methods Follow Up Evaluation," Persaud et al 33 describe and evaluate a National Institute of Environmental Health Sciences Worker Training Program (NIEHS WTP) pilot to train workers and employers about the extent of the opioid crisis, its impact on workers and work sites, that OUD is a brain disease and not a "moral failing," the impact of stigma, and preventive methods. The evaluation found that the training increased participant knowledge about opioids and opioid use disorder and its relationship to workplace injury and stress, and found that it more frequently influenced individual-as opposed to workplace-level actions.…”
Section: Importance Of Worker Training and Union-based Programsmentioning
confidence: 99%
“…These include: (1) lack of consensus on a definition for “healthy work”; (2) lack of consensus on the role of work stressors in ill health; (3) ideological beliefs about health and illness; (4) economic barriers to fixing unhealthy working conditions; (5) inadequate tools to diagnose sick and unhealthy workplaces; (6) lack of fully-tested, workable interventions and implementation strategies for workplace change; and (7) lack of enforceable standards to ensure that work is safe and promotes health. Additionally, the argument has been made that “the shortfall in ‘good jobs’ can be viewed as a massive market failure—a kind of gross economic malfunction and not just a source of inequality and economic exclusion [ 165 ].” These obstacles can be overcome in part with innovative research approaches, engaging different allies and partners, especially those outside the usual framework, particularly intermediary organizations [ 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Significant Emergent Themes From the Workhops And Ex4osh Con...mentioning
confidence: 99%